The Difference in the Effects of Brain Gym and Proprioceptive activity Methods on Gross Motor Skill Improvement in Children Aged 4-6 Years: The Difference in the Effects of Brain Gym and Proprioceptive activity Methods on Gross Motor Skill Improvement in Children Aged 4-6 Years - Lastyaningsih, Azizah Sukma; Lailatuz Zaidah; Asyhara Naela Arifin (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Background: Gross motor development in children aged 4-6 years is an important aspect that influences physical, social, and cognitive abilities. Gross motor disorders can hinder daily activities and child development. Brain Gym and Proprioceptive activity are two methods believed to improve gross motor skills, but their effectiveness has not been directly compared. Objective: This study aims to determine the differences in the effects of Brain Gym and Proprioceptive activity on the improvement of gross motor skills in children aged 4–6 years. Method: This study used a quasi-experimental design with a two-group pretest-posttest design. The sample consisted of 34 children aged 4–6 years at TK ABA Karangasem, Sleman, divided into the Brain Gym and Proprioceptive activity groups. Gross motor skills were measured using the Test of Gross Motor Development-2 (TGMD-2) before and after the intervention. The sampling technique used in this study was purposive sampling. Data analysis was performed using SPSS version 25. Data were analysed using paired sample t-tests and independent sample t-tests. Results: The results showed that Brain Gym significantly improved gross motor skills (p=0.000). Proprioceptive activity also had a significant effect (p=0.000). There was no significant difference between the two methods (p=0.140). Conclusion: Brain Gym and Proprioceptive activity effectively improve gross motor skills in children aged 4-6 years, but there is no significant difference between the two. Both methods can be used as alternative interventions to support the development of gross motor skills in children. Keywords: Brain Gym, Proprioceptive activity, Gross Motor Skills, Early Childhood, TGMD-2.